Phylogenomics of Acinetobacter species and analysis of antimicrobial resistance genes - Migliaccio, Antonella; Bray, James; Intoccia, Michele; Stabile, Maria; Scala, Giovanni; Jolley, Keith A.; Brisse, Sylvain; Zarrilli, Raffaele (Frontiers in Microbiology, 2023)
Non-baumannii Acinetobacter species are increasingly isolated in the clinical setting and the environment. The aim of the present study was to analyze a genome database of 837 Acinetobacter spp. isolates, which included 798 non-baumannii Acinetobacter genomes, in order to define concordance of classification and discriminatory power of 7-gene MLST, 53-gene MLST and singlenucleotide polymorphisms (SNPs) phylogenies. Bacterial genomes were manually selected from the PubMLST database. Pasteur MLST and ribosomal MLST were performed using BIGSdb software.Phylogenies were performed on Pasteur MLST or ribosomal MLST concatenated alleles, or SNPs extracted from core genome alignment. using RAxML under the GTR-GAMMA model. The phylogenetic trees were visualized using iTol v6 software. The resistance genes were detected using ABRicate software. The Pasteur MLST scheme was able to identify and genotype 72 species in the Acinetobacter genus, with classification results concordant with the ribosomal MLST scheme. The discriminatory power and the genotyping reliability of Pasteur MLST scheme was assessed in comparison to genome-wide SNP phylogeny on 535 non-baumannii Acinetobacter genomes assigned to Acinetobacter pittii, Acinetobacter nosocomialis, Acinetobacter seifertii and Acinetobacter lactucae (heterotypic synonym of Acinetobacter dijkshoorniae), which were the most clinically relevant nonbaumannii species of the A. baumannii group. The Pasteur MLST and SNP phylogenies were congruent at Robinson-Fould and Matching cluster tests and grouped genomes into four and three clusters in A. pittii, respectively, and one each in A. seifertii. Also, A. lactucae genomes were grouped into one cluster within A. pittii genomes. The SNP phylogeny of A. nosocomialis genomes showed a heterogeneous population and did not correspond to Pasteur MLST phylogeny, which identified two recombinant clusters. The antimicrobial resistance genes belonging to at least three different antimicrobial classes were identified in 91 isolates assigned to 17 distinct species in the Acinetobacter genus. Also, the presence of a class D oxacillinase, which is a naturally occurring enzyme in several Acinetobacter species, was found in 503 isolates assigned to 35 Acinetobacter species. In conclusion, Pasteur MLST phylogeny of non-baumannii Acinetobacter isolates coupled with in silico detection of antimicrobial resistance is important to study the population structure and epidemiology of Acinetobacter spp. isolates.